2020
DOI: 10.1002/ehf2.12722
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of insulin‐like growth factor binding protein‐7 and early identification of acute heart failure

Abstract: Aims Concentrations of insulin-like growth factor binding protein-7 (IGFBP7) have been linked to abnormal cardiac structure and function in patients with chronic heart failure (HF), but cardiovascular correlates of the biomarker in patients with more acute presentations are lacking. We aimed to determine the relationship between IGFBP7 concentrations and cardiac structure and to evaluate the impact of IGFBP7 on the diagnosis of acute HF among patients with acute dyspnoea. Methods and results In this pre-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
0
18
1
Order By: Relevance
“…In our study there was a significant correlation between IGFBP7 and NTproBNP concentration in patients with IHD. According to previous findings, it seems that left ventricular filling pressure may be an important trigger for IGFBP7 expression and release because of its strong independent association with an increased left atrial volume index (LAVI) [ 25 , 26 ]. We have not assessed ejection fraction (EF) in our research, but our previous findings showed no statistically significant differences of IGFBP7 concentrations between low-EF (<50%) and high-EF (>50%) patients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study there was a significant correlation between IGFBP7 and NTproBNP concentration in patients with IHD. According to previous findings, it seems that left ventricular filling pressure may be an important trigger for IGFBP7 expression and release because of its strong independent association with an increased left atrial volume index (LAVI) [ 25 , 26 ]. We have not assessed ejection fraction (EF) in our research, but our previous findings showed no statistically significant differences of IGFBP7 concentrations between low-EF (<50%) and high-EF (>50%) patients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 One study reported IGFBP7 as a possible biomarker of acute HF, improving the diagnosis in patients presenting with acute dyspnoea. 12,13 Gandhi et al reported that low IGFBP7 levels were predictive of event-free survival in patients with reduced ejection fraction. 14 Furthermore, IGFBP7 also presented as a potential marker of HF with preserved ejection fraction (HFpEF).…”
Section: Introductionmentioning
confidence: 99%
“…IGFBP7 was first found to be up‐regulated in mouse HF models and in patients with HF and cardiac hypertrophy 10,11 . One study reported IGFBP7 as a possible biomarker of acute HF, improving the diagnosis in patients presenting with acute dyspnoea 12,13 . Gandhi et al reported that low IGFBP7 levels were predictive of event‐free survival in patients with reduced ejection fraction 14 .…”
Section: Introductionmentioning
confidence: 99%
“…96 Pro-inflammatory cytokines also trigger the release of other factors such as insulin-like growth factor binding protein-7 (IGFBP-7). Elevated serum levels of IGFBP-7 are associated with left atrial remodelling and diastolic dysfunction in patients with acute dyspnoea (with or without HF) 97 and in HFpEF patients, 98 as well as with a higher risk of cardiovascular events including mortality. 98 The pro-inflammatory alarmins S100A8 and S100A9 play a role in cardiac remodelling after MI.…”
Section: Immune Cells and Inflammationmentioning
confidence: 99%